William Dunbar and the Querelle des Femmes: A Response to the Roman de la Rose - Lucy Hinnie (Etudes Epistémè)
This paper examines two established works by the Scottish poet William Dunbar (c. 1460-1513) which appear in the 1568 Bannatyne manuscript: “The Golden Targe” and “Sen that I am Presoneir” (also known as “Beauty and the Prisoner”).1 Rather than simply rereading the familiar steps of the debate, I argue that Dunbar exploits his mastery of genre and style in order to subvert the usual terms of the querelle debate and reignite discourse in a Scottish context. In particular, Dunbar’s use of language is analysed, in terms of its appeal to the senses in his construction of gender. Ultimately I suggest that rather than two distinctly separate and stylistically opposed poems, one can read the “Targe” and “Presoneir” as a pair of cognate poems, a stylistic parallel to the disjointed dual authorship of the “Rose.